2013
DOI: 10.1136/bjophthalmol-2013-303601
|View full text |Cite
|
Sign up to set email alerts
|

Examining the association between age-related macular degeneration and motor vehicle collision involvement: a retrospective cohort study

Abstract: Background Little is known about motor vehicle collision (MVC) risk in older drivers with age-related macular degeneration (AMD). The purpose of this study is to examine associations between MVC involvement and AMD presence and severity. Methods In a retrospective cohort study pooling the samples from four previous studies, we examined associations between MVC rate and older drivers with early, intermediate, or advanced AMD as compared to those in normal eye health. MVC data were based on accident reports ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…98 These and other studies concluded that AMD patients self-regulate by changing driving habits, for example, avoiding driving at night, in unfamiliar areas or over long distances 99100…”
Section: Resultsmentioning
confidence: 92%
“…98 These and other studies concluded that AMD patients self-regulate by changing driving habits, for example, avoiding driving at night, in unfamiliar areas or over long distances 99100…”
Section: Resultsmentioning
confidence: 92%
“…Few studies have assessed the crash risk and driving performance of older drivers with AMD with inconclusive findings. Studies have failed to find a link between AMD and increased crash risk, 14 , 15 indeed, drivers with intermediate levels of AMD had significantly lower crash rates than those with normal vision, 15 which was suggested to arise from driver self-regulation. 12 , 13 Simulator studies of small numbers of drivers with AMD suggest impairments in some aspects of driving ability, including delayed braking times, slower speeds, and more lane crossings, compared with age-matched controls.…”
mentioning
confidence: 99%
“… 21 , 22 Contrary to default expectations, older drivers with intermediate AMD were found to have a reduced risk of collision involvement in one small study. 23 Also, self-regulatory driving practices may change at older age; 24 for example, drivers reduce their mileage as they age and avoid driving in the dark, as well as using routes well-known to them with the result that they have fewer accidents than their younger counterparts. 19 Additionally, men are more likely to be behind the steering wheel at an older age than females 25 who have a higher prevalence of AMD, thus distorting the conclusions drawn from the sex distribution of license holders.…”
Section: Resultsmentioning
confidence: 99%